Diffuse Leiomyomatosis: Complete Myomectomy for Innumerable Small Nodules to Achieve Fertility Sparing and Childbearing - Konishi, Ikuo (The Surgery Journal, 2020)
Diffuse leiomyomatosis is a rare condition among benign smooth muscle neoplasms of the uterus, being defined as innumerable small myomatous nodules that mainly occur in the submucosal area. Young women with this disease suffer from menorrhagia, pains, and infertility. It is essential to perform extensive myomectomy after opening the endometrial cavity by a deep, median, longitudinal incision of the uterine corpus, followed by careful suture and reconstruction of the uterus for fertility spearing and childbearing in young women with this disease. So far, there have been no experiences of the uterine rupture during pregnancy even after such myomectomy, but Caesarean section is recommended for safe delivery.
Keywords: diffuse leiomyomatosis; extensive myomectomy; longitudinal incision of uterus; GnRH agonist; MRI; junctional zone